The effective of the flipped e – learning and the reinforced e – learning to the growth of the reflective thinking and the habits of mind at the students - Mowaffaq Abdul -Aziz Al-Hisnawi; Hussien Jarad Al – Waely (Zanco Journal of Humanity Sciences)
The aims of the research is known the effective of the flipped e – learning and the reinforced e – learning to the growth of the reflective thinking and the habits of mind at the students . The sample is (75 ) students in the first class in the electrical techniques department in technical institute in Nasirriayh . The subject is the theoretical electrical installation and the tools of the research are the reflective thinking test and the habits of mind test . The in depended variables are the flipped e – learning and the reinforced e – learning and the depended variables are the reflective thinking and the habits of mind . At first we applied the reflective thinking test and the habits of mind test and analysis their results and beginning teaching the control group by the traditional method and the first experimental group by the flipped e – instruction before the lecture and the second experimental group by the reinforced e – learning after the lecture to six weeks . After that we re - applied the reflective thinking test and the habits of mind test . The finding is supremacy the second experimental group than the first experimental group and than the control group in the reflective thinking and the habits of mind .